Use and appreciation of Mycenaean pottery in the Levant, Cyprus and Italy (1600-1200 BC) (Amsterdam archaeological studies, 2002)
Front Cover; Contents; Preface; Part I Introduction; Part II The Levant; Part III Cyprus; Part IV The central Mediterranean; Part V Conclusions; Tables; Maps; Catalogues; References; Index